Incidence of bean anthracnose in Western Kenya and its management using aqueous extract of Aloe vera - Wilkister , Mogita, G.; O. Julius , Ochuodho; S. Linet, Gohole; E. Esther , Arunga; Billy , Makumba (African Journal of Education,Science and Technology (AJEST), 2017)
High seed exchange and frequent resistance breakdown continue to be a challenge in managing seed borne fungi Colletotrichum lindemuthianum in Western Kenya farm saved bean seeds. Continuous pathogen surveillance can enable timely development and application of effective environment friendly mitigation strategies. The objective of this study was to determine the presence C. lindemuthianum on farm-saved bean seeds collected from seven different regions of Western Kenya and its possible control using aqueous plant extracts at different concentration in comparison to traditional fungicides. Systematic random sampling method was used to collect 196 farms saved bean seeds from farmers in the agro-ecological zones within the regions for four seasons between 2008 and 2010. Incidence was scored for each sampled seed lot. Water extract of Aloe vera was screened in vitro for antifungal activities against C. lindemuthianum using poison food technique. Both incidence and inhibitory data were subjected to analysis of variance using GenStat® computer package. The sampled eight seed varieties namely Red haricot (GLP- 585), Mwitemania GLP X92, Yellow (KAT B 1), Rose coco (GLP-288), White, Rose coco (GLP-2), Brown and Mwezi moja (GLP-1004) had high and significantly difference (p≤0.05) anthracnose incidences. Variety GLP 585 had the highest incidence (53.1%) whereas GLP 2 had the lowest (28.7%). Aqueous extract from Aloe vera plant exhibited a higher antifungal activity at all concentration levels (30, 25 and 20%) tested and compared well with the standard synthetic fungicide; Mancozeb. There is high disease incidence in the farm saved seeds in Western Kenya and this could be due to high seed exchange and the warm, humid environment. However, farmers should be encouraged to use environment friendly, affordable and effective aqueous plant extract of Aloe vera.